Personalised Professional Development in Teaching and Learning in Higher Education - Seo Hong Lim; Lyndon Lim; Che Yee Lye; Wei Ying Rebekah Lim (Trends in Higher Education, 2025)
Despite the affordances of professional development (PD) in teaching and learning in facilitating quality teaching and contributing to students’ learning outcomes, there is merit in exploring educators’ needs by enabling conditions to further develop their existing knowledge and practices. In fact, it is vital that PD in teaching and learning in higher education (HE) actively engages and meets instructor individual needs. This paper explores PD within the HE context and identifies corresponding categories common and in relation to quality teaching. Based on the review, most PD in teaching and learning could be identified within one of four categories that contribute to quality teaching: (1) assessment approaches; (2) instructional approaches; (3) communication and delivery approaches; and (4) affective responses. Equally important, instructor agency should be supported by encouraging instructors to identify and manage their PD needs via validated measures, which this review found lacking within the literature. With the expectation that such a measure would provide insights into the refinements of current PD in teaching and learning provisions, and enable HE institutions to facilitate PD in teaching and learning to better meet and fulfil instructor individual needs, it is recommended that such a measure be developed and deployed to identify instructors’ needs.